Філософське обгрунтування бзпеки життєдіяльності - Нетудихатка, О. Ю.; Нетудыхатка, О. Ю.; Netudyhatka, О. (My University, 2011)
The article analyzes the main philosophical writings, underlying understanding of role and importance of safety of human life. Life safety – integrated science because it has many connections with other sciences and therein lies its richness and complexity. Person, depriving the difﬁ culties of life, no objections, having no points of resistance, gradually weakens, atrophies and becomes a weak link in this world organization and thinking – interrelated concepts underlies the proper management and rational mode of life.
Нетудихатка О. Ю. Філософське обгрунтування бзпеки життєдіяльності / // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С. 26 - 35.
Keywords: безпека життєдіяльності; філософія; философия; безопасность жизнедеятельности; philosophy; Life Safety